Use Of Zoom Meeting Applications to Memorize the Qur’an Online - Firman Firman; Regar Alef; Musiion Eric (Journal International Inspire Education Technology, 2022)
Memorizing the Qur’an is something that is recommended for Muslims, because the Qur’an is a way of life for Muslims, as time goes on, new innovations emerge to make it easier for Muslims to memorize the Qur’an. Various facilities are used to memorize the Qur’an, one of which is the Zoom meeting application. During the pandemic, which required students, especially State College for Islamic Studies Batusangkar, to study remotely. One of the media used is the Zoom meeting application, especially in the Tahfizh Al-Qur’an course. The purpose of this study is to describe the use of the Zoom meeting application to memorize the Qur’an online. This research was conducted on students of the Batusangkar State Islamic Institute. The research method is using qualitative methods with data collection methods, namely by observation and interviews. The results of this study are using the Zoom meeting application to memorize the Qur’an online is very useful as a learning medium for students / lecturers in memorizing the Qur’an in the Tahfizh Al-Qur’an course with the guidance of Ustad or Ustadzah or lecturers Tahfizh course supervisor with a distance learning system (online).